Considerations for head and neck oncology practices during the coronavirus disease 2019 (COVID‐19) pandemic: Wuhan and Toronto experience. Issue 6 (27th April 2020) - Wu, Vincent; Noel, Christopher W.; Forner, David; Zhang, Zhi‐Jian; Higgins, Kevin M.; Enepekides, Danny J.; Lee, John M.; Witterick, Ian J.; Kim, John J.; Waldron, John N.; Irish, Jonathan C.; Hua, Qing‐Quan; et al.
Abstract: The practices of head and neck surgical oncologists must evolve to meet the unprecedented needs placed on our health care system by the Coronavirus disease 2019 (COVID‐19) pandemic. Guidelines are emerging to help guide the provision of head and neck cancer care, though in practice, it can be challenging to operationalize such recommendations. Head and neck surgeons at Wuhan University faced significant challenges in providing care for their patients. Similar challenges were faced by the University of Toronto during the severe acute respiratory syndrome (SARS) pandemic in 2003. Herein, we outline our combined experience and key practical considerations for maintaining an oncology service in the midst of a pandemic.